Bronchial asthma in the era of personalized medicine - A. Kh. Ibisheva; M. R. Shakhgireeva; A. B. Khildikharoeva; L. S. Uspanova; S. A. Shamsadova; L. V.-M. Dzhabrailova (Сибирский научный медицинский журнал, 2025)
Bronchial asthma is a growing burden on the health system worldwide, mainly affecting population of low-income countries. The widespread growth of morbidity has a significant negative impact on the quality of life of patients. The lack of radical treatment of asthma for many years can be explained by a lack of understanding of the mechanisms of its development. Currently, the heterogeneity of bronchial asthma is recognized, which is reflected in numerous risk factors. Advances in various aspects of the pathogenesis of this complex disease contribute to the development of new and more effective therapeutic approaches. Understanding the phenotyping and endotyping of asthma is an important aspect on which the effectiveness of a particular biological drug depends. Timely diagnosis and well-chosen therapy prevent the progression of the disease and allow achieving a long-term remission of bronchial asthma. The long-term history of studying the disease etiopathogenesis has brought progressive changes in the effectiveness of its treatment. The purpose of this work is to review the phenotypic features of bronchial asthma, as well as individualized treatment methods for severe asthma, prognostic and monitoring biomarkers of biological drugs. The search was conducted using PubMed, and EMBASE databases. The following keywords were used: “bronchial asthma”, “asthma phenotypes”, “asthma endotypes”, “asthma biomarkers”.